Association of intestinal and systemic inflammatory biomarkers with immune reconstitution in HIV+ patients on ART - Mariana del Rocio Ruiz-Briseño; Judith Carolina De Arcos-Jiménez; Sarah Ratkovich-González; Karina Sánchez-Reyes; Luz A. González-Hernández; Jaime F. Andrade-Villanueva; Monserrat Alvarez-Zavala (BMC, 2020)
Abstract Background HIV infection is characterized by CD4+ T-cells depletion related to gut damage, microbial translocation, immune activation and intestinal and systemic low-grade inflammation. With the use of antiretroviral treatment, these alterations in HIV+ patients reach similar levels to HIV- controls. However, almost 20% patients have deficient immune reconstitution of CD4+ T-cells, which make them more susceptible to develop non-AIDS and AIDS comorbidities. Methods HIV+ patients on ART, with sustained virologic control were grouped according to their immune reconstitution as: immunological responders (n = 18) and immunological non-responders (n = 18); also, HIV- controls were enrolled (n = 14). CD4+ and CD8+ T-cell activation (HLA-DR+ and CD38+ single and co-expression) were measured by flow cytometry. Serum levels of sCD14, sCD163, lipopolysaccharide, I-FABP, sST2, as well as fecal levels of calprotectin, lactoferrin and secretory IgA were evaluated by ELISA. Levels of C-reactive protein were determined by a high sensibility singleplex bead-based immunoassay. Serum and fecal concentrations of proinflammatory cytokines were quantified by multiplex bead-based immunoassay. Results HLA-DR+ and CD38+ co-expression, as well as median fluorescence intensity in CD4+ and CD8+ T-cells subpopulations was greater in immunological non-responders group, after normalization and fold change calculation. Similarly, this group presented higher levels of sCD14, C-reactive protein, as well as fecal calprotectin and lactoferrin. Furthermore, both HIV+ groups showed elevated levels of proinflammatory cytokines in stool. Conclusions Our data suggests that despite the virologic control, HIV+ patients under treatment with deficient immune reconstitution showed elevation of both innate and T-cells immune activation, as well as intestinal and systemic inflammation. However, some patients with CD4+ T-cells count above 350 cells/μL also presented these alterations. Future studies are necessary to evaluate the dynamics of multiple systemic and intestinal biomarkers in diverse types of HIV+ patients, as such as their clinical impact.